2021
DOI: 10.1021/acs.jafc.1c05677
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Exploration of Quinoline Derivatives against Phytopathogenic Fungi Inspired by Quinine Alkaloids

Abstract: Enlightened from our previous work of structural simplification of quinine and innovative application of natural products against phytopathogenic fungi, lead structure 2,8-bis­(trifluoromethyl)-4-quinolinol (3) was selected to be a candidate and its diversified design, synthesis, and antifungal evaluation were carried out. All of the synthesized compounds Aa1–Db1 were evaluated for their antifungal activity against four agriculturally important fungi, Botrytis cinerea, Fusarium graminearum, Rhizoctonia solani,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 42 publications
1
38
0
Order By: Relevance
“… On the other hand, for the fungicidal acethydrazide compounds reported in the literature, the plasma membrane contraction and separation from the cell wall in the treated fungal cells could be clearly found by TEM observation, while the specific target was unclear (Figure ). In this project, it was also found that the plasma membrane was shrunk seriously and separated from the cell wall (Figure ). Therefore, transcriptomics and metabolomics measurements were performed to further elucidate the mechanism of action of acethydrazide compound C4 .…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“… On the other hand, for the fungicidal acethydrazide compounds reported in the literature, the plasma membrane contraction and separation from the cell wall in the treated fungal cells could be clearly found by TEM observation, while the specific target was unclear (Figure ). In this project, it was also found that the plasma membrane was shrunk seriously and separated from the cell wall (Figure ). Therefore, transcriptomics and metabolomics measurements were performed to further elucidate the mechanism of action of acethydrazide compound C4 .…”
Section: Resultsmentioning
confidence: 66%
“…In terms of agricultural fungicidal activity, for example, Wang’s group reported benzoic hydrazides ( 1 ) containing a 1,2,3-triazole group as potential SDH inhibitors, Yang and co-workers synthesized pyrazole hydrazides ( 2 ) bearing a 1,3,4-oxadiazole core as agrochemicals against plant fungus and Ye’s group prepared 1,2,3-triazole hydrazide derivatives ( 3 ) exhibiting anti-phytopathogenic activity . Similarly, other literature has also successively reported the application of hydrazide structures controlling agricultural pathogens, such as compounds 4 – 6 listed in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…The change in permeability of S. sclerotiorum membrane treated with compound 6c 2 was determined by a conductivity method 41 . The mycelial disks of S. sclerotiorum (5 mm) were placed in 20.0 mL of Potato Dextrose Broth ( PDB) liquid medium at 27 °C and shaken at 140 rpm to culture for 4 days.…”
Section: Methodsmentioning
confidence: 99%
“…DMSO (1%) in 10 mL water was used as a blank control. All treated samples were placed in a light incubator at 25 °C and 100% relative humidity for 9 d. All assays were performed at least in triplicate using conventional methods [ 51 ].…”
Section: Methodsmentioning
confidence: 99%